Dinamika Komunikasi Organisasi Dalam Perumusan Kebijakan Publik Di Era Digitalisasi - La Ode Abdul Musawir; Kasman Muslimin; La Ode Ahmad Darwin; Rosikah; Iwan P (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
This study aims to determine the dynamics of organisational communication in public policy formulation in the era of digitalisation. The method used is literature analysis with a literature review. Data collection was conducted through a systematic search of scientific literature in related articles, books, documents, and journals that significantly discuss the research theme, namely the dynamics of organisational communication in public policy formulation in the era of digitalisation. The technique used in this study was the literature method. The literature review method plays an important role in formulating the theoretical basis and conceptual framework. A comprehensive analysis of literature relevant to the dynamics of organisational communication, public policy formulation, and the era of digitalisation was conducted to understand the changes that have occurred. A qualitative approach was used to analyse data obtained from various scientific papers, books, research reports, and other reliable sources. The results obtained are that the development of digital technology has brought about major changes in policy communication patterns. Whereas in the past communication emphasised one-way delivery, there has now been a transformation towards interactive dialogue between the government and the public. This shift has made policy communication not only a means of information, but also an arena for public participation that determines the legitimacy and quality of decisions. mooth communication will minimise misunderstandings and unify the vision among the parties involved. This integration has a direct implication on the organisation's ability to convey policies to the public. When internal communication runs well, external strategies will also be more accepted by the public. The process of formulating public policy further emphasises the role of communication as a central element. The initial stage of formulation determines the direction of implementation, making accurate information and public participation essential. Decisions based solely on normative considerations without regard to social realities tend to lose their appeal. Openness in communication can help bridge the gap between ideals and the real needs of society. It is at this point that communication becomes the benchmark for policy success. Digitalisation brings great opportunities as well as complex challenges. Rapid access to information makes the public more critical of government decisions, but the rapid flow of messages can lead to confusion, polarisation and even misinformation. The government needs to manage information carefully so that messages are not distorted and policy objectives remain clear. Readiness to face digital dynamics is a prerequisite for success in maintaining policy legitimacy. The layered flow of information in the digital space also gives rise to a diversity of interpretations. A policy can be understood in different ways, leading to lengthy debates. This phenomenon shows that the substance of a policy cannot be separated from the way it is communicated. The government is required to formulate messages that are clear, simple, and easy to understand in order to reduce the potential for misinterpretation. The more transparent the communication, the greater the chance that the policy will be widely accepted. Digital communication is the key to the success of public policy. Digitalisation is not merely technological progress but also a transformation in building dialogue, trust, and transparency between the government and the public. Governments that are able to manage digital communication appropriately will find it easier to gain legitimacy. Ignoring public opinion has the potential to weaken policy authority. This conclusion emphasises that open, participatory, and responsive communication is the foundation for successful policy in the digital age.